Helicobacter pylori colonization in Nepal; assessment of prevalence and potential risk factors in a hospital-based patient cohort. (December 2016) - Ansari, Shamshul; Gautam, Rajendra; Nepal, Hari; Subedi, Shankar; Shrestha, Sony; Mandal, Fuleshwar; Rimal, Brihaspati; Chhetri, Muni
Abstract Background Helicobacter pylori, a gram-negative bacterium, can cause gastritis, peptic and duodenal ulcers. It is considered an important public health problem for both developed and developing world. This bacterium is classified as the class 1 carcinogen because it can cause cancer. Methods A hospital based study was conducted at Chitwan Medical College Teaching Hospital (CMCTH) from May to October 2014. Stool samples were collected from the suspected patients and were subjected to detection of theH. pylori stool antigen (HpSAg) following the procedures recommended by the manufacturer. A standard questionnaire on the potential risk factors was also designed and completed. Result HpSAg was detected in 16 % of suspected patients. The children up to 10 years of age were found to be highly infected (36 %). The patients living in urban area were found more susceptible to developH. pylori infection (P < 0.05). Tea drinking and repeated eating habit (more than twice a day) were listed as the important factors that can limit theH. pylori infections significantly (P < 0.05). Conclusion In this hospital based study, a significant rate of prevalence was evaluated. However, we recommend a community based extensive study to reveal the real scenario ofH. pylori infection in Nepalese populations.